Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Problem Based Learning di Kelas IV Sekolah Dasar - Hikmah Avriani; Rifda Eliyasni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This research is backed by the less optimized integrated thematic learning that resulted in learners less understanding of the material so as to impact learning outcomes. This research aims to describe the improvement of integrated thematic learning outcomes using Model Problem Based Learning (LBL) in students of class IV SDN 19 Kampung Olo Padang. This type of research is PTK with a qualitative and quantitative approach. Research Data in the form of observation and test results. The study carried out two cycles. Research subject is teacher and student class IV. The results of RPP observations on the I cycle gained an average of 81.94% (B) increased in cycle II gained an average of 91.66% (AB). The teacher aspect of the cycle I with an average of 82.14% (B) increased in cycle II by an average of 96.42% (AB). The student aspect on the I cycle with an average of 82.14% (B) increases in cycle II to 96.42% (AB). The study results with an average of 90.17% (B). This proves a problem based learning approach can improve student learning outcomes.